2017
DOI: 10.5455/ijlr.20170713074142
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Immunopathological Studies on Naturally Infected Cases of Porcine Circovirus-2 in Kerala

Abstract: Porcine circovirus-2 (PCV2) is one such emerging viral pathogen of concern as it is involved in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…A numerical decrease of erythroid cells and mild increase of myeloid cells were noticed on bone marrow cytology. The M: E ratio in PCV-2 positive animals was 1.2: 1 whereas that in apparently healthy pigs was 0.9:1. previous reports of Keerthana et al (2017) and Sairam et al (2019). In the present study, cases suggestive by gross and histopathological lesions were confirmed by PCR.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…A numerical decrease of erythroid cells and mild increase of myeloid cells were noticed on bone marrow cytology. The M: E ratio in PCV-2 positive animals was 1.2: 1 whereas that in apparently healthy pigs was 0.9:1. previous reports of Keerthana et al (2017) and Sairam et al (2019). In the present study, cases suggestive by gross and histopathological lesions were confirmed by PCR.…”
Section: Resultsmentioning
confidence: 53%
“…The pooled tissue samples from mesenteric lymph nodes, tonsils, lungs and bone marrow (Keerthana et al, 2017) were collected and investigated. Lymphoid organs and nonlymphoid organs were collected in 10% neutral buffered formalin for histopathological evaluation (Suvarna et al, 2019).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation